Interaction of Salmonella spp. with the Intestinal Microbiota - Ahmer, Brian M.; Gunn, John S. (Frontiers in Microbiology, 2011)
Salmonella spp. are major cause of human morbidity and mortality worldwide. Upon entry into the human host, Salmonella spp. must overcome the resistance to colonization mediated by the gut microbiota and the innate immune system. They successfully accomplish this by inducing inflammation and mechanisms of innate immune defense. Many models have been developed to study Salmonella spp. interaction with the microbiota that have helped to identify factors necessary to overcome colonization resistance and to mediate disease. Here we review the current state of studies into this important pathogen/microbiota/host interaction in the mammalian gastrointestinal tract.